COMPARATIVE STUDY OF ZONING SYSTEMS AND TRAFFIC FLOW PATTERNS AT MERAK FERRY PORT IN 2023 AND 2025 - Sulistiyono, Noor; Setiawan, Bambang; Firzatullah, Raden Muhamad; Erwan, Erwan; Salsabila, Anisa Aulia (IWJ : Inland Waterways Journal, 2025)
The Merak Ferry Port is a major ferry transportation route in Indonesia, serving the Merak-Bakauheni crossing. Based on observations and analysis, several issues were identified related to the zoning system and vehicle traffic flow patterns in 2023, such as the combination of executive and regular vehicle lanes in a single service, limited parking capacity, and the presence of crossings between vehicles that hamper the smooth loading and unloading process. This study aims to analyze and compare the zoning system and traffic flow patterns at the Merak Ferry Port in 2023 and 2025 to evaluate the effectiveness of the changes made. This study employed a qualitative descriptive method, with data collection techniques through field observation and analysis of official documents. The results indicate that changes to the 2025 zoning system, including the separation of executive and regular vehicle lanes and the addition of ready-to-load parking capacity, have a positive impact on the smooth flow of vehicles and the effectiveness of space management. Overall, these zoning changes have successfully improved the existing system and increased operational efficiency and service quality at the Merak Ferry Port.